Ekho nedeli . Ekho nedeli . Echoes of the Week . Эхо недели - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion about how Russia's political course might depend on the economic situation. Featured in the program: Chubais, Anatolii Borisovich (Politician) Contributors: Pototskii, Igor' (Anchor) Дискуссия о зависимости политического курса России от экономической ситуации. В программе участвуют: Чубайс, Анатолий Борисович (Политик) Создатели: Потоцкий, Игорь (Ведущий/Ведущая)